MEMAKNAI PLURALISME DAN KERUKUNAN UMAT BERAGAMA DENGAN EMOTIONAL AND SPIRITUAL QUOTIENT (ESQ) - Siti Aisyah (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2019)
Indonesia is a country made up of diverse people, tribes, ethnic or social groups, beliefs, religions, and cultures, different from one region to another region that dominates Indonesian cultural treasures. With the increasingly diverse array of community and culture, of course, each individual community has different desires. people from different areas with different backgrounds, social structure, and the characters are different, have different views in a way thinking in the face of their own lives and problems